Mul'tikul'turalizm i olimpijskij sport - Bulatova, M. (Science in Olympic Sport, 2018)
Objective. To study multiculturalism as a phenomenon that attracts heightened attention in the context of globalization of the modern world and the possibilities of the Olympic sport to expand theoretical concepts and practical activities focused on ensuring equality in the rights and freedoms for various groups of the population. Methods. Historical methods of obtaining knowledge, content analysis, expert survey, system integrative approach, logical method. Results. The specifi cs of the philosophy of Olympism and the actual practice of Olympic sport create a natural environment, in which qualities are displayed such as respect for the rights of participants and objective assessment of their achievements regardless of racial, ethnic, religious, cultural or other background. This, however, does not mean the absence of the need forappropriate education and development as an integral part of the Olympic education and requires the inclusion of a multicul-tural education in its content. The paper provides characteristics of the concept of `multiculturalism` as a phenomenon ensuring the achievement of equality in the rights and freedoms of various groups of the population, the mutual enrichment of cultures through the development of mutual understanding, mutual respect and tolerance, and bringing people together on the cul-tural bases. The types and characteristics of multiculturalism were analyzed along with its relation to the globalization of the world community, the risks and contradictions. The relationship between multiculturalism and the philosophy of Olympism was proved, the possibilities of the Olympic sport for ensuring the rights and interests of diff erent groups of population were identi-fi ed. On the basis of the data about multiculturalism in the USA, the possibilities of sport were shown to implement its policy,to strengthen self-awareness and self-identifi cation, to develop pride and solidarity of minorities subjected to discrimination. The development of multiculturalism as exemplifi ed by the Olympic sport was shown; the role of the Olympic education in the implementation of multiculturalism policy is characterized, the prospects of its development in this direction were analyzed. Conclusion. High performance sport and, especially the Olympic sport and the Olympic movement, create special conditions for the implementation of a balanced multiculturalism policy both at the international and national levels due to the specifi cs determined by the philosophy of Olympism, strict rules of the competition and identifi cation of the winners, and exceptional popularity and mass character of Olympics in the world